Metode Pengasuhan Orang Tua dalam Membentuk Karakter Religius Anak di Jorong Parit Panjang Kenagarian Lubuk Basung Kecamatan Lubuk Basung - Intan Afuadda; Rini Rahman (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study contains the method of parenting in shaping the religious character of children in jorong Parit Panjang Kenagarian Lubuk Basung Kecamatan Lubuk Basung. Then it has the aim of knowing the parenting method in shaping the religious character of children. The research was conducted using a descriptive qualitative method. The data collection techniques used in this study include observation, interviews and documentation in searching for data related to the title of the research that is sourced directly from the family or community in Jorong Parit Panjang. The data analysis technique used in this research is through the stages of data reduction, data display, and conclusion drawing/verification. As for the results of this study, parenting methods are divided into habituation methods and exemplary methods.